NASAL CARRIAGE OF MULTI-DRUG RESISTANT PANTON VALENTINE LEUKOCIDIN POSITIVE STAPHYLOCOCCUS AUREUS IN HEALTHY INDIVIDUALS OF TUDUN-WADA, GOMBE STATE, NIGERIA - Onanuga, Adebola; Adamu, Ocholi Jonathan; Odetoyin, Babatunde; Hamza, Jabir Adamu (African Journal of Infectious Diseases (AJID), 2020)
Background: Panton-Valentine Leucocidin (PVL)-producing Staphylococcus aureus strains have been implicated in serious community-associated invasive infections and their increasing multidrug resistance is a major global health concern. Thus, we investigated the carriage of PVL gene and antimicrobial resistance profile of nasal S. aureus isolates from healthy adults in Tundu-Wada, Gombe State, Nigeria. Methods: A total of 262 nasal samples of healthy adults were obtained and cultured. The isolates were identified as S. aureus by standard conventional methods and Polymerase Chain Reaction (PCR) amplification of their 16S rRNA gene. Antimicrobial susceptibility testing was performed by the disc diffusion technique and the presence of mecA and PVL genes was determined by PCR analysis. Results: The overall nasal colonization of S. aureus was 17.6%. The prevalence of haemolysin and biofilm production among the isolates was 25 (54.3%) and 42 (91.3%) respectively. Only 2(4.3%) and 5(10.9%) possessed mecA and PVL genes respectively but none haboured these two genes. All the isolates were resistant to amoxicillin but were highly susceptible (93.7%) to gentamicin. The prevalence of multi-drug resistance (MDR) among the isolates was 45.7% and all PVL-producing isolates were MDR while one of the isolates with mecA gene exhibited extensively-drug resistance. The predominant antibiogram among MDR isolates was AML,SXT,E. Conclusion: This is the first report of nasal colonization of MDR PVL-producing S. aureus in healthy adults in Gombe, Northeastern Nigeria. It highlights the importance of routine surveillance of healthy populations to provide useful strategies for containing the spread of virulent multidrug-resistant organisms within the community.